Postmodern Interpretations of Satie's Parade - Albright, Daniel (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
If postmodernism can be considered ahistorically, as a stylistic category operative at any time and in any place, then there are many older works that suddenly seem to speak strongly to our present age. This paper argues the case for taking Erik Satie as a postmodernist: his music is marked by bricolage (the E-driophthalma movement from Embryons desséchés, 1913, borrows a theme, according to the score, "from a celebrated mazurka by Schubert"); by polystylism (the cabaret songs written for Vincent Hyspa, or Parade with its quotation from Irving Berlin); and by materialism of the signifier (what Satie calls furniture music).